Táticas de enfrentamento a fatores estressores no cotidiano de trabalho de profissionais de saúde de uma Unidade de Pronto Atendimento - ISABELLA CRISTINA MORAES CAMPOS (2022)
The difficulties faced in the daily work of an Emergency Care Unit (UPA) are risk factors for occupational stress. However, some workers manage to minimize it by adopting individual or collective coping measures as defense mechanisms to reduce suffering. Objective: To analyze the tactics of coping with stressors in the daily work of health professionals at a UPA in a municipality in the interior of Minas Gerais, Brazil. Method: This is a descriptive, cross-sectional case study with a qualitative approach. Michel de Certeau's theoretical framework of everyday life was adopted. Data collection took place between August 2020 and January 2021 and unsystematic observations, interviews and survey of UPA documents were carried out, which allowed the triangulation of information sources. The sample consisted of 31 workers and the inclusion criteria were being 18 years of age or older, belonging to a professional health category and working in the institution for at least six months. Those who were on vacation, on leave and who participated in the pilot study were excluded. Data were organized in MaxQda ® 2020 and submitted to Content Analysis according to Bardin. The ethical precepts defined by Resolution No. 466/2012 were complied with. Results: Thematic categories were defined: "The proper place impregnated by circumstantial and strategic normative situations", "The propulsive/encouraging stressors of paths practiced by the UPA health professionals" and "The tactics of coping with stressors". The UPA has national, state and municipal regulations, as well as internal norms and routines, which are configured as strategies, but it was possible to identify the tactics that professionals adopted to overcome the difficulties that arose in their daily work. The following were highlighted as occupational stressors in daily work: difficulties in patient transfers, large number of non-urgent care, work overload, scarcity of material and human resources, relationships with users and professionals and violence. In addition, with the pandemic, there were changes in the daily life of the UPA and other stressors emerged, such as fear of contamination of oneself and family, use of personal protective equipment (PPE), low testing, removal of professionals, possible lack of medicines and stigmatization of health professionals. The availability of PPE, the drop in the number of visits, support from the leadership and guidance and training were the protectors against stress. Final considerations: In the UPA, there were no strategies for the prevention of occupational stress, which required that professionals use tactics to overcome the challenges of real work and adopt individual and collective measures to face it. This study can contribute to the adoption of measures to prevent suffering, with improved quality of life, better working conditions and service to users.